f(x)=4x-7 and g(x)=6x 1. f(x)+g(x) 2. f(x)-g(x) 3. g(x)*f(x) Please help Thanks :D
M math92 New member Joined Oct 7, 2008 Messages 1 Oct 7, 2008 #1 f(x)=4x-7 and g(x)=6x 1. f(x)+g(x) 2. f(x)-g(x) 3. g(x)*f(x) Please help Thanks
L Loren Senior Member Joined Aug 28, 2007 Messages 1,299 Oct 7, 2008 #2 Example: f(x)=x and g(x)=2x-3 1. f(x)+g(x) = x + 2x-3 = 3x-3 2. f(x)-g(x) = x -(2x-3) = x -2x + 3 =-x+3 3. g(x)*f(x) =x(2x-3) = 2x[sup:2kzq3a2p]2[/sup:2kzq3a2p]-3x
Example: f(x)=x and g(x)=2x-3 1. f(x)+g(x) = x + 2x-3 = 3x-3 2. f(x)-g(x) = x -(2x-3) = x -2x + 3 =-x+3 3. g(x)*f(x) =x(2x-3) = 2x[sup:2kzq3a2p]2[/sup:2kzq3a2p]-3x
M Mrspi Senior Member Joined Dec 17, 2005 Messages 2,128 Oct 7, 2008 #3 math92 said: f(x)=4x-7 and g(x)=6x 1. f(x)+g(x) 2. f(x)-g(x) 3. g(x)*f(x) Please help Thanks Click to expand... You know what f(x) is, and what g(x) is....so, 1) f(x) + g(x) = (4x - 7) + 6x Now, simplify the right side by combining like terms. 2) f(x) - g(x) = (4x - 7) - 6x Again, simplify the right side. 3) f(x) * g(x) = (4x - 7)*6x Use the distributive property to remove the parentheses on the right side.
math92 said: f(x)=4x-7 and g(x)=6x 1. f(x)+g(x) 2. f(x)-g(x) 3. g(x)*f(x) Please help Thanks Click to expand... You know what f(x) is, and what g(x) is....so, 1) f(x) + g(x) = (4x - 7) + 6x Now, simplify the right side by combining like terms. 2) f(x) - g(x) = (4x - 7) - 6x Again, simplify the right side. 3) f(x) * g(x) = (4x - 7)*6x Use the distributive property to remove the parentheses on the right side.